Dynamic RNA modifications in gene expression regulation - Roundtree, Ian A. (Cell, 2017)
Over one hundred types of chemical modifications have been identified in cellular RNAs. While the 5’ cap modification and the poly(A) tail of eukaryotic messenger RNA play key roles in regulation, internal modifications are gaining attention for their roles in mRNA metabolism. The most abundant internal modification is N(6)-methyladenosine (m(6)A), and identification of proteins that install, recognize, and remove this and other marks have revealed roles for mRNA modification in nearly every aspect of the mRNA lifecycle, as well as in various cellular, developmental, and disease processes. Abundant noncoding RNAs such as transfer RNAs, ribosomal RNAs and spliceosomal RNAs are also heavily modified and depend on the modifications for their biogenesis and function. Our understanding of the biological contributions of these different chemical modifications is beginning to take shape, but it’s clear that in both coding and noncoding RNA, dynamic modifications represent a new layer of control of genetic information.